Peste, trevas e telas: Camus, Conrad e Dying Light - Hessel, Lucas Mendes (2021)
The present dissertation proposes to reflect on the approximation between the narratives that reside both in literary works, and as contained in a more recent media, in video games. The intention of this work is to analyze aesthetic productions, in dialogue, in different supports, considering the works Heart of Darkness (2002), by Joseph Conrad, The Plague (2008), by Albert Camus and the video game Dying Light (2015), by Polish developer Techland, drawing parallels between coexisting and intertextual diegeses, even if in different supports and codes and in textual games with different reception and interaction statutes. Therefore, in the first chapter of this text, we will do, from the perspective of Lucia Santaella (2014), the conceptualization of the reader, both of literature and that subject who reads and interacts with a narrative that is displayed on screens, through his interaction with the virtualized content that consists of a video game. We will also conceptualize, under the vision of Johan Huizinga (2019), what the game consists of, not only as a consequence of the existence of human society, but in its essence, as an undeniable reality above men. As a bridge between games and literature, we will have the contribution of Alan Richard da Luz (2010) and his studies on the video game, which will allow us to prove how narrative possibilities exist in the virtualization of games, which is the essence of video games. On the virtual and its manifestations, we will have Pierre Lévy (1996) elucidating important questions to the theme. At the beginning of this dissertation, we will exemplify how intertext and dialogue between videogames and literature can take place. Then, this work selected principally to video games, its logic and internal mechanics, as well as certain characteristics inherent to the media it represents, observed as possibilities of reading in the various titles available to consumers of video games. Ahead, we analyze dialogical and intertextual elements existing between three works already stated, two literary and one electronic. Again, the objective of the analysis is to recognize the intertextual and dialogical movements that transit between the three works, realizing that the video game, like literature, is capable of reading, interpreting and reflecting the one who reads, proving its inherent artistic value and its impact in contemporary society.